Penggunaan Metode Contextual Teaching And Learning (CTL) Untuk Meningkatkan Minat Belajar Matematika Siswa Kelas VII di MTsS YATI Kamang Mudik TP. 2023/2024 - Sakina Rahmi Hamsia; Pipit Firmanti; Mhd. Padil (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This research was motivated by the mathematics learning process it was found that students lacked interest in learning, so that their learning outcomes were considered low and not in accordance with the KKM set by the school. The aim of this research is to determine and describe students' interest in learning mathematics and self-confidence using the Contextual Teaching and Learning approach. This type of research is Qualitative Descriptive. The subjects of this research were 18 students of class VII MTsS YATI Kamang Mudik, taking 6 subjects for interviews. The results of this research show that students' interest in learning mathematics in the interested category is 73.57%. Increasing interest in learning makes student learning outcomes better. This can be seen from the results of the students' pre-test and post-test with an increase of 24.01%. Students also feel happy with the approach used, because students think that the Contextual Teaching and Learning approach can make it easier for students to understand the material taught by the teacher. The higher the student's interest in learning and self-confidence, the better the learning outcomes they get. A learning approach using Contextual Teaching And Learning can increase interest in learning mathematics and good student learning outcomes.